DISORDERS OF THE AUTISM SPECTRUM IN CHILDREN A NEW APPROACH TO THE PROBLEM (Academicia Globe: Inderscience Research, 2021)
The problem of autism spectrum disorders is one of the most urgent in modern psychiatry, due to the steady increase in the number of children suffering from early childhood autism. Recently, there has been an increase in the number of patients diagnosed with autism, in part due to changed approaches to diagnosis.